2017
DOI: 10.1002/2016ms000837
|View full text |Cite
|
Sign up to set email alerts
|

Transient aspects of the Hadley circulation forced by an idealized off‐equatorial ITCZ

Abstract: This paper presents analytical solutions of large‐scale, zonally symmetric overturning circulations in the tropical free troposphere forced by transient diabatic heating in the off‐equatorial intertropical convergence zone (ITCZ). The dynamics are discussed in the context of the time‐dependent meridional circulation equation arising in an equatorial β‐plane model. The solutions of these differential equations contain terms for the slow, quasi‐balanced part of the response and terms for the transient, zonally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The subsidence flanking the ITCZ in these cross sections is indeed stronger to the south, consistent with that finding (Figures b and c). We therefore speculate that the low‐midlevel and upper‐level diurnal maxima in subsidence flanking the ITCZ are the transient response to nocturnal latent heating and daytime shortwave heating, respectively (Gonzalez et al, ). More work is required, however, to investigate this transient, remote response.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The subsidence flanking the ITCZ in these cross sections is indeed stronger to the south, consistent with that finding (Figures b and c). We therefore speculate that the low‐midlevel and upper‐level diurnal maxima in subsidence flanking the ITCZ are the transient response to nocturnal latent heating and daytime shortwave heating, respectively (Gonzalez et al, ). More work is required, however, to investigate this transient, remote response.…”
Section: Resultsmentioning
confidence: 93%
“…This is consistent with in situ observations of the Hadley cell described by Ciesielski et al (). Gonzalez et al () showed through theoretical arguments that transient heating in an ITCZ situated north of the equator will cause stronger compensating subsidence and inertia‐gravity wave activity on its southern side. The subsidence flanking the ITCZ in these cross sections is indeed stronger to the south, consistent with that finding (Figures b and c).…”
Section: Resultsmentioning
confidence: 99%
“…The latitude of ITCZ precipitation migrates seasonally, both in a global sense, and within each ocean basin (Donohoe et al, 2013;Koutavas & Lynch-Stieglitz, 2004;Richter et al, 2017;Sikka & Gadgil, 1980;Wei & Bordoni, 2018). The ITCZ acts as a waveguide for tropical convective disturbances (Ferreira & Schubert, 1997;Gonzalez et al, 2017) and helps maintain ocean circulations that sustain biological activity and promote ocean CO 2 uptake (Xie & Philander, 1994;Kessler, 2006).…”
Section: Introductionmentioning
confidence: 99%